Cupping Therapy for Migraine: A PRISMA-Compliant Systematic Review and Meta-Analysis of Randomized Controlled Trials. (25th March 2021) - Seo, Jihye; Chu, Hongmin; Kim, Cheol-Hyun; Sung, Kang-Keyng; Lee, Sangkwan
Abstract : Background . Migraine is a common reason for primary headache disorders. Cupping is a frequently used traditional intervention for controlling pain including migraine. There have been no systematic reviews on the clinical effects of cupping on migraine. Objective . This systematic review and meta-analysis aimed to evaluate the effectiveness of cupping therapy for migraine. The search strategy was built for the presence of related keywords, such as "migraine" and "cupping therapy", in the title and abstract of research articles indexed in the MEDLINE, EMBASE, CENTRAL, and other databases. The randomized controlled trials (RCTs) of cupping therapy for migraine were searched and selected from inception to May 2019. We searched eight databases including PubMed, EMBASE, Cochrane Central Register of Controlled Trials. The selection process and the quality assessment were performed by 2 authors independently. The meta-analysis was conducted and qualitative analysis was also performed. Results . 218 studies were identified, and 6 RCTs were enrolled in this review. In comparison to drugs, wet cupping showed a higher total effective rate (TER). In the dry cupping plus acupuncture, the result of TER showed more effectiveness (RR 1.05, 95% CI 0.99 to 1.12, P = 0.13 ) compared with acupuncture alone, but there was no statistically significant difference. In qualitative analysis, the results showed wet cupping plus drugs treatment could quickly relieve pain and significantly improve patients' quality of life and wet cupping could reduce headache pain. Conclusion . Cupping therapy could be effective for the treatment of migraine. However, the qualities of the evidence were low, so well-designed RCTs are needed to confirm the effectiveness of cupping. Systematic review registration: PROSPERO registration number is CRD42017054979 .